Efficacy of keratometric values obtained from Sirius topographer® in nidek axial length-scan® for intraocular lens calculation after penetrating keratoplasty - Kandemir Beşek, Nilay; Aşık Nacaroğlu, Şenay; Kırgız, Ahmet; Öztürk Karabulut, Gamze; Ökmen, Helin; Ahmet, Sibel (Elsevier B.V., 2023)
Background: To evaluate the accuracy of keratometric values obtained from Scheimpflug (Sirius) topography using Nidek AL-Scan optical biometry (OB) for intraocular lens (IOL) power calculating after penetrating keratoplasty (PK). Methods: Thirty eyes of 26 patients were included in this study. The demographic information, complete ophthalmic examination, IOL calculation technique, and its effect on final refractive results were evaluated. Results: The mean age of the patients was 52.76 ± 16.20 years. The mean K readings using Nidek AL-Scan OB, mean simulated K (SimK) (3mm), and mean pupillary power (MPP) (4.5mm) K readings using Sirius were 41.92 ± 5.05 D, 42.99 ± 5.78 D, and 43.30±6.23 D (p= 0.515). Conclusions: Both devices correctly calculated IOL power after PK; however, Sirius SimK (3mm) gave the lowest mean absolute error (MAE) results and can be safely used for IOL power calculation.
Efficacy of keratometric values obtained from Sirius topographer (R) in nidek axial length-scan (R) for intraocular lens calculation after penetrating keratoplasty
Keywords: Cataract Surgery; Optical Biometry; Penetrating Keratoplasty; Scheimpflug Topography